What explains the growing global demand for cash? - Sayuri Shirai; Eric Alexander Sugandi (Asian Development Bank Institute (ADBI), 2019)
Demand for cash is generally known to be influenced by several factors−including transaction motive used for payment, opportunity cost, precautionary motive (such as crisis period), and other motives (such as aging and demand from abroad). In recent years, cashless payment methods have increasingly become prevalent in the world through various conventional tools (such as credit cards, debit cards) and innovative convenient financial services using mobile phones and smart phones. Nevertheless, cash in circulation has been rising in many economies, especially after the global financial crisis. The rising trend is prevalent even in advanced economies, notwithstanding that the public normally has had full access to bank accounts and credit cards for a long time and other cashless payment tools in recent years. The low interest rate environment appears to have affected the rising trends. Meanwhile, emerging/developing economies continue to issue cash significantly partly because their nominal GDP growth rates have been greater than those of advanced economies. Interestingly, the People's Republic of China (PRC) experienced a decline in the ratio of cash in circulation to nominal GDP, suggesting greater access by residents to bank accounts and/or other non-bank cashless payment services. This paper first focuses on the time-series movements of cash in circulation (in terms of the amount and nominal GDP) for 22 economies for the period 2000-2018. It also investigated the movements of banknotes in circulation differentiated by denomination for six economies whose data were available. Several empirical analyses with regards to the cash demand function (controlling for the transaction motive by using the ratio of cash in circulation to nominal GDP as a dependent variable) were then conducted for the Euro Area, Japan, and the United States separately. Subsequently, an empirical analysis on cash demand covering all the 22 economies for the period 2000-2018 was performed. The paper found that the opportunity cost proxied by the central bank policy rates and age-related variable were the two most important robust determinants for cash demand. Namely, cash demand tends to grow with a decline in the policy rates and with an advancement of aging.
Keywords: E41; E52; E58; 330; money demand; monetary policy; central bank